Fucoxanthin inhibits tumour‐related lymphangiogenesis and growth of breast cancer. Issue 3 (16th January 2019) - Wang, Jia; Ma, Yanhong; Yang, Jingshi; Jin, Lu; Gao, Zixiang; Xue, Lingyun; Hou, Lin; Sui, Linlin; Liu, Jing; Zou, Xiangyang
Abstract: Tumour lymphangiogenesis plays an important role in promoting the growth and lymphatic metastasis of tumours. The process is associated with cell proliferation, migration and tube‐like structure formation in lymphatic endothelial cells (LEC), but no antilymphangiogenic agent is currently used in clinical practice. Fucoxanthin is a material found in brown algae that holds promise in the context of drug development. Fucoxanthin is a carotenoid with variety of pharmacological functions, including antitumour and anti‐inflammatory effects. The ability of fucoxanthin to inhibit lymphangiogenesis remains unclear. The results of experiments performed as part of this study show that fucoxanthin, extracted from Undaria pinnatifida (Wakame), inhibits proliferation, migration and formation of tube‐like structures in human LEC (HLEC). In this study, fucoxanthin also suppressed the malignant phenotype in human breast cancer MDA‐MB‐231 cells and decreased tumour‐induced lymphangiogenesis when used in combination with a conditional medium culture system. Fucoxanthin significantly decreased levels of vascular endothelial growth factor (VEGF)‐C, VEGF receptor‐3, nuclear factor kappa B, phospho‐Akt and phospho‐PI3K in HLEC. Fucoxanthin also decreased micro‐lymphatic vascular density (micro‐LVD) in a MDA‐MB‐231 nude mouse model of breast cancer. These findings suggest that fucoxanthin inhibits tumour‐induced lymphangiogenesis in vitro and in vivo, highlighting its potential use as an antilymphangiogenic agent for antitumour metastatic comprehensive therapy in patients with breast cancer.